Urbanizing Rural Zimbabwe: Growth Points 37 Years on, Opportunities and Challenges Case of Zhombe in the Midlands Province of Zimbabwe - Henry Mabika; Naome Rajah (IJTRD, 2023)
The designation of growth points created a ray of hope and promise for development of the hinterland. With government promising to invest in infrastructure there was a lot of hope that growth points would be the epi-center of activities in rural Zimbabwe. Attraction of both public and private investment was envisaged, but that was not to be. In Zhombe the little that government put up like the grain marketing board and the cotton company deports are the only visible developments since independence apart from the small scale welding and carpentry shops. Thirty seven(37) years after designation Zhombe growth point is actually showing signs of decline rather than development. The gold deposits around Kwekwe district that are being exploited by small scale gold panners have not been able to help develop Zhombe. To invite investment to growth points like Zhombe, Zimbabwe needs to involve the grassroots in planning as well as assist gold panners and gold buyers become serious business people in areas they are operating.